The influence of “small private online course + flipped classroom” teaching on physical education students’ learning motivation from the perspective of self-determination theory - Hu, Ti; Zhang, Meng-long; Liu, Hong; Liu, Jun-cheng; Pan, Si-jia; Guo, Jiang-hao; Tian, Zong-en; Cui, Lei (Frontiers in Psychology, 2022)
Objective: To enhance the learning motivation of college physical education students and improve their learning outcomes. Based on the perspective of self-determination theory, this study explores the influence of " SPOC+ flipped classroom" teaching on the learning motivation of students majoring in physical education and profoundly analyzes the influencing factors and promotion paths of learning motivation under this model. Methods: Four classes (64 students) of physical education majors in a university were selected and randomly divided into an experimental group (34 students) and a control group (30 students). The experimental group received "SPOC+ flipped classroom" teaching, the control group received traditional teaching. Before and after the 16 weeks intervention, learning motivation, teacher support perception, basic psychological needs satisfaction, and academic emotions of the 64 students were measured, and the data were analyzed by repeated-measures Analysis of Variance and partial least square regression. Results: (1) The instructional intervention reduced non-regulation, external regulation, and introjected regulation, while increasing identified regulation, intrinsic regulation, and self-determination level in the students. The levels of non-regulation, external regulation, identified regulation, and self-determination level were also significantly different from those of the control group. (2) After the intervention, the scores of support for autonomy, support for competence, support for relatedness, and need for relatedness in the experimental group were significantly higher than those in the control group. (3) Support for autonomy, support for competence, support for relatedness, need for competence and need for relatedness positively predicted the self-determination level, and intrinsic regulation and identified regulation negatively predicted non-regulation, external regulation, and introjected regulation. Conclusion: "SPOC+ flipped classroom" teaching has a positive impact on students' learning motivation of basketball skills and promotes students' motivation autonomy. The improvement of support for autonomy, support for competence, support for relatedness, need for competence and need for relatedness may be related to the improvement of learning motivation of college students majoring in PE. "SPOC+ flipped classroom" teaching enables students to obtain more demand satisfaction by giving them more demand support, while demand support and demand satisfaction can promote the internalization of learning motivation so that students can maintain high autonomy motivation.